2009
DOI: 10.1176/ps.2009.60.5.601
|View full text |Cite
|
Sign up to set email alerts
|

Medicaid Prescription Drug Policies and Medication Access and Continuity: Findings From Ten States

Abstract: These associations indicate that more effective Medicaid prescription drug management and financing practices are needed to promote medication continuity and improve treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
0
16
1
Order By: Relevance
“…54 Such changes may have increased drug substitutions and/or wait times for medications. 55 Our study found no association between Massachusetts health reform and decreased access to primary care for privately or publicly insured CSHCN, despite well-publicized concerns about primary care shortages. 16,21 This finding may be because, although some CSHCN see family practitioners, the majority (78%) of CSHCN receive care from pediatricians and may be protected from delays observed in adult primary care.…”
Section: Discussioncontrasting
confidence: 74%
“…54 Such changes may have increased drug substitutions and/or wait times for medications. 55 Our study found no association between Massachusetts health reform and decreased access to primary care for privately or publicly insured CSHCN, despite well-publicized concerns about primary care shortages. 16,21 This finding may be because, although some CSHCN see family practitioners, the majority (78%) of CSHCN receive care from pediatricians and may be protected from delays observed in adult primary care.…”
Section: Discussioncontrasting
confidence: 74%
“…In fact, very few studies that assessed out-comes of such programs have been published. One study of such a program demonstrated that use of nonpreferred antipsychotics was reduced by up to 13.9% (9) but was associated with an unintended increase in antipsychotic treatment discontinuities among Medicaid recipients and did not change total pharmacy reimbursements (10,11). Prior authorization with step therapy—the required use of one medication before trying another—achieved the intended goal of reducing use of second-generation agents but was associated with increased outpatient treatment (12).…”
Section: Strategies To Improve Quality Of Prescribingmentioning
confidence: 99%
“…Given the large number of children with unknown race/ethnicity, a problem common to Medicaid claims data studies, 19,20 we imputed race data for our final models by using SAS PROCMI and all available independent and dependent variables. To verify our analyses, we compared results to regression models by using race data without imputation and found similar results.…”
Section: Discussionmentioning
confidence: 99%